Pemahaman Hadis Tentang Bencana (Sebuah Kajian Teologis terhadap Hadis-hadis tentang Bencana) - Muhammad Alfatih Suryadilaga (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Disaster is something always happens around human life. Those catastrophic events occured one after anothers and the intensity increases in contemporary times. In that context, it is necessary to attempt selfreflection and build knowledge about the disaster in religious perspective. Actually, the disaster in the Qur'an has been widely described. However, the hadith of the Prophet Muhammad as the highest authority after the Qur'an, which serves as an explanatory (al-bayan), describes how the disaster happened, what causes it, and how humans should behave for facing the disaster. This brief article will review these matters with the theological approach.